2019
DOI: 10.1002/humu.23872
|View full text |Cite
|
Sign up to set email alerts
|

A functional variant in the miR‐142 promoter modulating its expression and conferring risk of Alzheimer disease

Abstract: Noncoding RNAs have been widely recognized as essential mediators of gene regulation. However, in contrast to protein‐coding genes, much less is known about the influence of noncoding RNAs on human diseases. Here we examined the association of genetic variants located in primary microRNA sequences and long noncoding RNAs (lncRNAs) with Alzheimer disease (AD) by leveraging data from the largest genome‐wide association meta‐analysis of late‐onset AD. Variants annotated to 5 miRNAs and 10 lncRNAs (in seven distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 74 publications
(124 reference statements)
1
17
0
Order By: Relevance
“…Likewise, a systematic analysis integrating GWAS, gene expression and DNA methylation data indicated multiple long non-coding RNAs associated with cardiometabolic disorders [358]. Besides, functional genomics by integrating GWAS data and various experimental studies using human iPS-derived neuronal progenitor cells and miR-142 knockout mice demonstrated the role of miR-142 in the pathogenesis of Alzheimer's disease [359]. An independent study further identified that the clinical spectrum of early Alzheimer's disease pathology is explained by different biological pathways, in particular, the endocytosis, clathrin/AP2 adaptor complex, and immune response pathways, that are independent of apolipoprotein E (APOE) [360].…”
Section: Integrative Omics and Systems Epidemiologymentioning
confidence: 99%
“…Likewise, a systematic analysis integrating GWAS, gene expression and DNA methylation data indicated multiple long non-coding RNAs associated with cardiometabolic disorders [358]. Besides, functional genomics by integrating GWAS data and various experimental studies using human iPS-derived neuronal progenitor cells and miR-142 knockout mice demonstrated the role of miR-142 in the pathogenesis of Alzheimer's disease [359]. An independent study further identified that the clinical spectrum of early Alzheimer's disease pathology is explained by different biological pathways, in particular, the endocytosis, clathrin/AP2 adaptor complex, and immune response pathways, that are independent of apolipoprotein E (APOE) [360].…”
Section: Integrative Omics and Systems Epidemiologymentioning
confidence: 99%
“…Column 'SNP prob' indicates the mean fine-mapping probability for the SNP; the SpliceAI score is the maximum splicing probability for donor gain/loss or acceptor gain/loss, with nonzero values highly enriched for splicing effects; the DeepSEA functional significance score represents the significance above expectation for chromatin feature changes, as well as evolutionary conservation, with lower values more significant. References for specific SNPs are shown 2,7,9,14,40,41,[60][61][62][63][64][65][66][67][68][69] . confidence variants also include a well-known missense SNP in PILRA 41 , and a splicealtering missense SNP in CD33 7 .…”
Section: Fine-mapping Identifies Credibly Causal Variantsmentioning
confidence: 99%
“…Variants of miR-142-3p have recently been associated with a reduced risk of Alzheimer's disease (49). Building on in vitro and in vivo data implicating miR-142-3p in the regulation of novel oligodendrocyte gene networks, we examined miR-142-null mice by WGCNA to directly assess whether our significant oligodendrocyte modules (M4, M8) or tauopathy modules (T4, T20, T25) were affected by absence of the miR (Fig.…”
Section: Cortical Oligodendrocyte and Tauopathy Gene Network Are Associated With Genetic Deletion Of Mir-142mentioning
confidence: 99%